2016
DOI: 10.19044/esj.2016.v12n24p362
|View full text |Cite
|
Sign up to set email alerts
|

Etude De La Qualité Agronomique Et Biochimique De Quelques Variétés De Niébé (Vigna Unguiculata (L) Walp (Fabaceae) Provenant De La Côte d’Ivoire

Abstract: Cowpea is a legume consumed in Côte d'Ivoire. There are many cultivars whose seeds are widely available. This study aimed to determine some agronomic and physicochemical characteristics of some cowpea cultivars in order to identify differences and if possible select the best for appropriate uses. The study included 16 cultivars; the agro-morphological variability was assessed on the basis of eight parameters. The results showed that the accessions N21DR, N18ZR, N10BBrp produced more seeds in a relatively short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The results of analyses highlighted a high variability within the studied varieties at the qualitative and quantitative levels. Indeed, the high values of the coefficient of variation for several characters and the number of modalities per qualitative character would indicate a high heterogeneity within the studied material (Boyé et al 2016). This heterogeneity between varieties is apparent in the principal component analysis with its two components to reflect the diversity within cowpea varieties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of analyses highlighted a high variability within the studied varieties at the qualitative and quantitative levels. Indeed, the high values of the coefficient of variation for several characters and the number of modalities per qualitative character would indicate a high heterogeneity within the studied material (Boyé et al 2016). This heterogeneity between varieties is apparent in the principal component analysis with its two components to reflect the diversity within cowpea varieties.…”
Section: Discussionmentioning
confidence: 99%
“…The number of seeds per pod, ranging from 14 to 59 seeds, is higher than that obtained by Egbadzor et al (2014), which varied from 9 to 21 seeds. According to Boyé et al (2016), the variability observed within varieties concerning the number of seeds per pod reflects their ability to mobilize assimilates to reserve structures. Concerning the weight of 100 seeds, Khan et al (2010) showed that the variability obtained between varieties depends on genotype and climatic factors.…”
Section: Discussionmentioning
confidence: 99%